Evaluation of atherogenic indices in patients with endometrioma: A case-control study - Gamze Yilmaz; Onur Acar (Elsevier, 2024)
Objective: To evaluate the cardiovascular risk status of patients with endometriosis using serum lipid parameters and atherogenic indices. Materials and methods: The study was retrospective, single-centric, case-control study, involving a total of 190 women, including 95 cases and 95 control groups. Blood parameters, inflammatory markers as serum pan-immune-inflammation value, systemic immune-inflammation index, systemical inflammation-response index, and the atherogenic indices as Atherogenic Index of Plasma (AIP), Castelli Risk Index I and II (CRI-I and II), and the Atherogenic Coefficient (AC) were calculated. Results: Triglyceride (TG) levels among serum lipid parameters (103.09 ± 54.17 vs 77.52 ± 23.37, p < 0.001) and Atherogenic Index of Plasma (AIP) values (0.25 ± 0.24 vs −0.13 ± 0.19, p < 0.001) were significantly higher in endometriosis patients than in the control group. Patients with endometriosis had 2.31 times higher high-risk AIP values (1.23-4.33, p = 0.008). Conclusion: Our study indicates that patients with endometriosis are at a heightened risk for developing a proatherogenic lipid profile and an elevated atherogenic index of plasma (AIP). Given the often delayed diagnosis of endometriosis and the extended period of chronic exposure to the disease, patients should be evaluated for atherosclerotic cardiovascular diseases during clinical follow-ups.